The Interplay of Developmental and Dialogical Epistemologies - Engeström, Ritva (Outlines. Critical Practice Studies, 2014)
The paper examines Developmental Work Research (DWR) –based interventions from the perspective of qualitative research. The motive comes from two directions. First, the DWR has turned the scientific focus quite early toward trans- and interdisciplinary collaboration and methodology. However, the approach has been recognized more through its intervention theory and practice, and less as a particular research design, which can contribute to qualitative research strategy. Second, there is a trend towards one-dimensional evidence-based approach, which foregrounds standards of methods in the context of new public management of science. The paper views developmental interventions as representing an alternative way of research with the practice-inspired methodology offering practice-based source of evidence. To examine more this alternative the paper deals with the question how developmental interventions can be considered research designs that make context and dialogue the basis of research. Considering the DWR methodology, the paper argues that although dialogue is central in actualizing an intervention, dialogical epistemology has remained as underdeveloped in the approach. The paper focuses on dialogicality and sense making in developmental interventions examining the processes of anchoring and objectification, object in relation to personal sense, and how the individual and collective processes are linked and coexist in the complex relationship between pragmatic activity and social processes. As illustrations of ideas, pieces of data from conducted developmental interventions are used.